The influence of accounting information disclosure on foreign direct investment in nigerian listed companies / Oyerogba Ezekiel Oluwagbemiga - Oluwagbemiga, Oyerogba Ezekiel (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
Reduction of information asymmetry is of interest to the investors, standard setters, financial analysts and other users of financial statement. However, the extent to which adoption of international financial reporting standard improved the quality of disclosure of accounting information in the financial statement and whether the disclosure of accounting information results into an increase in the inflow of foreign direct investment into any developing economy is uncertain. The study used publicly disclosed information in audited financial statement to investigate the link between accounting information disclosure and foreign direct investment in Nigerian listed companies. Using both descriptive statistics and inferential statistics on a sample of 142 companies drawn from the 186 companies listed on the Nigerian stock exchange with a total of 710 observations, the study document that disclosure of accounting information does not have a significant influence on the flow of foreign direct investment. Also, adopting a multivariate regression analysis, was found that foreign investors paid less attention to overall accounting information disclosure. It is also evident that they did not pay a keen interest to the equity information, cashflow information, segment information and dividend information.